Macrophages 2021
DOI: 10.5772/intechopen.92666
|View full text |Cite
|
Sign up to set email alerts
|

New Tools for Studying Macrophage Polarization: Application to Bacterial Infections

Abstract: Macrophages are tissue immune cells involved in homeostasis and are considered as the first line of defense during bacterial infections. They are resident cells but may be recruited during inflammation and/or infection. Hence, their study is necessary not only to decipher innate immune mechanisms involved in bacterial infections but also to follow infected patients. Among the numerous functions of macrophages, their polarization into microbicidal or permissive cells has been an interesting concept to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The interaction of viruses like SARS-CoV-2 with macrophages induces their activation, which may lead to tissue damage and severe disease via the production of inflammatory and toxic mediators ( 9 ). As we previously demonstrated, macrophage activation can be stratified into M1 and M2 states using a combination of markers ( 11 , 43 , 44 ). It was recently reported that polarized M1 and M2 macrophages presented an inhibitory effects on SARS-CoV-2 infection ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of viruses like SARS-CoV-2 with macrophages induces their activation, which may lead to tissue damage and severe disease via the production of inflammatory and toxic mediators ( 9 ). As we previously demonstrated, macrophage activation can be stratified into M1 and M2 states using a combination of markers ( 11 , 43 , 44 ). It was recently reported that polarized M1 and M2 macrophages presented an inhibitory effects on SARS-CoV-2 infection ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some viruses are able to inhibit production of nitric oxide [38][39][40][41] or pro-inflammatory cytokines [42][43][44], suppress antigen presentation [45][46][47][48], or simply modulate the signaling pathways associated with polarization by inducing M2 phenotype [8,[49][50][51]. We previously addressed the role of macrophage polarization in bacterial infections [7,52]; the aim of the present talk is to assess the role of macrophage polarization in viral infections by selecting typical viral infections.…”
Section: Viral Infectious Diseases In Humansmentioning
confidence: 99%
“…Macrophages can be categorized into M1 or M2 profile according their inflammatory and immunoregulation role, respectively. 10,16 As pregnancy has been proposed to regulate a dynamic immunologic process, 17 a successful pregnancy requires a regulation of macrophage activation status during the different trimesters of pregnancy. 18 Dysregulation of macrophages from placenta has been associated to several pregnancy complications such as pre-eclampsia, miscarriage, chorioamnionitis and infection.…”
Section: Introductionmentioning
confidence: 99%
“…These functions are mediated by the ability of macrophages to modulate their inflammatory profile or their polarization profile through their high plasticity. Macrophages can be categorized into M1 or M2 profile according their inflammatory and immunoregulation role, respectively 10,16 . As pregnancy has been proposed to regulate a dynamic immunologic process, 17 a successful pregnancy requires a regulation of macrophage activation status during the different trimesters of pregnancy 18 .…”
Section: Introductionmentioning
confidence: 99%